2011
DOI: 10.1111/j.1945-1474.2011.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuity in Home Health Care: Is Consistency in Nursing Personnel Associated with Better Patient Outcomes?

Abstract: A growing body of evidence suggests that patients who receive coordinated and uninterrupted health care services have better outcomes, more efficient resource utilization, and lower costs of health care. However, limited research has considered whether attributes of continuity in home health care service delivery are associated with improved patient outcomes. The present study examines the relationship between one dimension of continuity of care, consistency in nursing personnel, and three patient outcomes: ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 14 publications
2
43
0
Order By: Relevance
“…Our results extend previous studies (Unroe et al, 2012;Allen et al, 2011;Ogunneye, 2014;Sandvik et al, 2013;Russell et al, 2011;Veilleux et al, 2014;Tuso et al, 2014;Neuman et al, F I G U R E 1 Flow chart demonstrating how the study sample was determined F I G U R E 2 Distribution of nursing homes by the composite star rating score. The composite score of the aggregated four measures showed approximately 67% of nursing homes were in a range of greater than two stars and less than four stars and 20% were in a range of greater than four stars | 5 of 10 2014), which focused on the association between nursing home performance and hospital readmissions at the patient level.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results extend previous studies (Unroe et al, 2012;Allen et al, 2011;Ogunneye, 2014;Sandvik et al, 2013;Russell et al, 2011;Veilleux et al, 2014;Tuso et al, 2014;Neuman et al, F I G U R E 1 Flow chart demonstrating how the study sample was determined F I G U R E 2 Distribution of nursing homes by the composite star rating score. The composite score of the aggregated four measures showed approximately 67% of nursing homes were in a range of greater than two stars and less than four stars and 20% were in a range of greater than four stars | 5 of 10 2014), which focused on the association between nursing home performance and hospital readmissions at the patient level.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have shown that nursing home performance may play an important role in hospital readmissions (Unroe, Greiner, Colón-Emeric, Peterson, & Curtis, 2012;Allen et al, 2011;Ogunneye et al, 2014;Sandvik, Bade, Dunham, & Hendrickson, 2013;Russell, Rosati, Rosenfeld, & Marren, 2011;Veilleux, Wight, Cannon, Whalen, & Bachman, 2014;Tuso et al, 2014;Neuman, Wirtalla, & Werner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to the managers, limiting the number of carers was a prerequisite for achieving continuity of care; interpersonal continuity appeared to be an ideal. It is a common presumption that patients prefer consistency of carers (Haggerty et al 2003, Woodward et al 2004, McLeod 2011 and it is also presumed that carer consistency enables quality care (Russell et al 2011). Experiencing continuity of care may also have a positive effect on the patientÕs psychosocial wellbeing (DÕErrico 2006).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…13,[19][20][21] Prior studies have largely focused on home health care use and services. [22][23][24][25][26][27][28] Although these studies have shown that rural areas used home health care services less frequently and that a single agency was more likely to serve areas in the Midwest and West, [22][23][24][25] it is largely unknown how much geographic variation there is in quality of agency performance. There could be regional contextual influences that lead to regional variation in addition to variation between individual agencies.…”
mentioning
confidence: 99%